PRb and CyclinD1 Complement p16 as Immunohistochemical Surrogate Markers of HPV Infection in Head and Neck Cancer. Issue 5 (May 2017) - Dreyer, Johannes H.; Hauck, Franziska; Barros, Mário H. M.; Niedobitek, Gerald
Abstract : Identification of human papillomavirus (HPV) association in head and neck squamous cell carcinoma (HNSCC) is important to identify patients with favorable disease course. However, molecular HPV detection is not universally available. p16 has been proposed as a surrogate marker for HPV infection in HNSCC but, use on its own may result in wrong assignment of some cases to the group of HPV-associated tumors. We have therefore studied 424 HNSCC cases with known p16 and HPV DNA polymerase chain reaction (PCR) status for expression of retinoblastoma protein (pRb) and CyclinD1 by immunohistochemistry using 6-tiered scales (0 to 5) and a combined score (0 to 10). Sixty-one of 424 cases showed overexpression of p16. Of these, 52 cases were HPV DNA-PCR-positive. HPV association strongly correlated with low expression scores for pRb and CyclinD1 individually (scores ⩽2) or combined (score sum ⩽4), whereas HPV-negative carcinomas showed widely distributed expression scores. High expression scores for pRb or for pRb/CyclinD1 were observed exclusively in HPV DNA-PCR-negative cases. Three of 9 p16-positive/HPV DNA-PCR-negative cases showed high expression of pRb and displayed a high combined pRb/CyclinD1 score. We conclude that HPV-positive HNSCC are characterized by p16 overexpression and low scores for pRb, CyclinD1, and a low combined pRb/CyclinD1 score. High pRb or combined pRb/CyclinD1 scores are strong indicators for HPV-negativity and may justify excluding these cases from further molecular HPV testing. Furthermore p16-positive/HPV DNA-PCR-negative cases show heterogeneous expression of pRb and CyclinD1, including high pRb or high combined pRb/CyclinD1 scores suggesting that at least some of these cases are truly HPV negative.